The nursery teacher in action : teaching 3, 4 and 5-year olds - Edgington, Margaret (London : Paul Chapman Pub., 1991)
The book is one of very few which present an in-depth view of the role of a nursery teacher in action.... the style of writing is clear and jargon-free, making this a useful reference book for trainee teachers as well as experienced practitioners' - Mentoring and Tutoring
Includes bibliographical references and indexes.
Keywords: Nursery schools -- Great Britain; Preschool teaching -- Great Britain; Preschool teachers -- Great Britain